A Review of 144 Cases of Dacryocystorhinostomy - Naeem Khattak, Mustafa Iqbal, Zaman Shah, Ibrar Hussain (Pakistan Journal of Ophthalmology, 2009)
Purpose: To determine the surgical outcome of blocked lacrimal pathway. Material and Methods: This is a retrospective study of 144 patients admitted in Naseer Teaching Hospital Peshawar from January 2005 to December 2007. Results: The age of the patients was in range from 06 to 60yrs. 45(31.25%) were male and 99(68.75%) were female. All of these cases were unilateral. 134(93.05%) of the total patients were operated under local anesthesia and the rest 10(6.94%) were under general anesthesia. The overall success rate was 62.5% in intubated patients and 93.75% without intubation Conclusion: External dacryocystorhinostomy is still the cheapest and effective surgical procedure.